Saturday night at the Speedway: class, race, gender and a ‘lynching’ - Roos, Neil (Acta Academica: Critical views on society, culture and politics, 2018)
This paper will reflect on some contemporary re- enactments of whiteness by a white subaltern crowd attending an oval track speedway meeting in central South Africa in 2017. It will also consider my role as ethnographer/observer, this latter aspect positioning the paper as a kind of ‘gonzo-ethnography’. I tracked several individuals including an ‘organic comedian’, a number of women and some children through what turned out to be a key event at the night’s sport, an act of crowd violence directed at three Bangladeshi men. This episode was spontaneous, populist and bottom-up, with evidence of strong gendered roles. It can best be described as a kind of organized disorder as the three racial outsiders were isolated, humiliated, and stripped of the veneer of common humanity; in other words, it bore the characteristics of a lynching, albeit in symbolic form. This carnival rendering of violence was central to the identity and coherence of the crowd that night. The violence on show was ironically of a kind which the apartheid state itself sought to police and prohibit among subaltern whites from as early as the 1950s, reminding us once again that whiteness, was never homogeneous or without internal tensions and fractures. I was part of the crowd, a white man. And in my silence, I became a participant. In closing I reflect on the moral problems raised by this gonzo-ethnography, of failing to follow Fanon’s example from Martinique and intervening vigorously in an act of racial violence, and on the possibilities and limits of insurgent history-writing.